The Political Opposition: Some Theoretical-Methodological Problems - Blagoeva, Blaga (Research Papers, 2023)
The article interprets the main theoretical analyzes of the political opposition at the level of its definition, place and role in the political process. The main goal of the study is to systematize the main classifications and models of political opposition in the scientific literature and to propose an author's definition of opposition. The ideas of leading scholars of political opposition such as Robert are subjected to analysis and interpretation. Dahl, Gita Ionesco and Isabel de Madariaga, Leonard Shapiro and Rudolf Tökes. Special attention is paid to the different models and types of opposition, as well as to the possible criteria for the classification of the political opposition. Based on the performed analysis, the author makes basic conclusions and generalizations related to the need for future theoretical analyzes and empirical studies of the political opposition.
Keywords: Political opposition; Models of opposition; Types of opposition; Parliamentary opposition; Dissidence